Efektivitas Ekstrak Umbi Bawang Putih (Allium sativum L.) untuk Mengendalikan Hama Crocidolonia pavonana F. pada Tanaman Sawi - Hasnah Hasnah; M. Ilyas Abubakar (Jurnal Agrista, 2007)
ABSTRACT. Crocidolomia pavonana F. is an important pest on mustards. Damage caused by this pest could be 100 percent if not controlled. Objective of the research was to find an effective concentration of garlic extract to control C. pavonana F. The research was the conducted at Experimental Farm of Agriculture Faculty, Syiah Kuala University, Darussalam Banda Aceh. Treatments were arranged by Completely Randomized Block Design (CRD) non factorial with 7 level concentrations based on LC50 of 20.69 ml L-1 or 20.69 percent. The concentrations of treatment were 10, 20, 30, 40, 50, 60, and 70 ml L-1 of water. The treatment was replication four times. The result showed that the garlic extracts were effective to control C. pavonana. Observation on larva mortality was carried out until the end of larva period of 3 day after application